Technological Innovations, Downside Risk, and the Modernization of Agriculture - Emerick, Kyle; de Janvry, Alain; Sadoulet, Elisabeth; Dar, Manzoor H. (The American economic review, 2016)
We use a randomized experiment in India to show that improved technology enhances agricultural productivity by crowding in modern inputs and cultivation practices. Specifically, we show that a new rice variety that reduces downside risk by providing flood tolerance has positive effects on adoption of a more labor-intensive planting method, area cultivated, fertilizer usage, and credit utilization. We find that a large share of the expected gains from the technology comes from crowding in of other investments. Therefore, improved technologies that reduce risk by protecting production in bad years have the potential to increase agricultural productivity in normal years.